Skills, division of labor and performance in collective inventions: Evidence from the open source software - Paola Giuri; Matteo Ploner; Francesco Rullani; Salvatore Torrisi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
This paper investigates the role of skills and the division of labor among participants in collective inventions. Our analysis draws on a large sample of projects registered at Sourceforge.net, the world's largest incubator of open source software activity. We test the hypothesis that the level of skills of participants and their skill variety are important for project performance. Skill heterogeneity across participants is in line with two fundamental organizational features of the open source development model: team work and modular design. We also explore the hypothesis whether the level of modularization of project activities is an important predictor of performance. Our econometric estimations show that both skill level and skill heterogeneity positively affect projects' survival and performances. However, the impact of skill diversity is non linear. Design modularity is also positively associated with the performance of the project.
Keywords: L86; O32; J24; 330; software; technological innovation; human capital; modularity; Qualifikation; Projektmanagement; Open Source